PENGARUH STRATEGI PEMBELAJARAN AKTIF THE POWER OF TWO TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS VII SMPN 4 SUTERA KABUPATEN PESISIR SELATAN TAHUN PELAJARAN 2012-2013 - Herni, Maiyuli; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2013)
The background of this research is result of studentsâs mathematic value that less cause they do not have a brave to ask and give argument. The purpose of this research to know the result of studentsâs mathematic value using The Power of Two as an active learning strategy better than the usual learning in seven class SMP N 4 Sutera. The kind of his research is experiment research. Population of this research is students in seven class SMP N 4 Sutera Period 2012-2013, consist of seven class. The choose is VII.I class as an experiment and VII. 3 class as a control class. The instrument is result of the test. The form test is essay with reliability test r11 = 0,79. Based on data analyzing, two sample is normal distributed and do not homogen, so using test. The concluded of this result of studentsâs mathematic value is using The Power of Two as an active learning strategy better than the usual learning in seven class SMP N 4 Sutera Period 2012-2013.